2022
DOI: 10.3390/molecules27092811
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Nanoparticles Loaded with Levodopa and Curcumin for Treatment of Parkinson’s Disease

Abstract: Background: Parkinson’s disease (PD) is the second most common age-related neurodegenerative disorder. Levodopa (L-DOPA) remains the gold-standard drug available for treating PD. Curcumin has many pharmacological activities, including antioxidant, anti-inflammatory, antimicrobial, anti-amyloid, and antitumor properties. Copolymers composed of Poly (ethylene oxide) (PEO) and biodegradable polyesters such as Poly (ε-caprolactone) (PCL) can self-assemble into nanoparticles (NPs). This study describes the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 91 publications
0
6
0
1
Order By: Relevance
“… 457 Recently, another group implemented polymeric micelles composed of polyethylene oxide and poly ε-caprolactone to co-deliver levodopa and curcumin as potential therapy for PD. 458 The system was modified with glutathione to enhance brain delivery due to its specific binding in BBB. 459 …”
Section: Neurodegenerative Diseases (Nds)mentioning
confidence: 99%
“… 457 Recently, another group implemented polymeric micelles composed of polyethylene oxide and poly ε-caprolactone to co-deliver levodopa and curcumin as potential therapy for PD. 458 The system was modified with glutathione to enhance brain delivery due to its specific binding in BBB. 459 …”
Section: Neurodegenerative Diseases (Nds)mentioning
confidence: 99%
“…According to Jin et al, curcumin was found to alleviate PD by energizing the BDNF/PI3k/Akt transduction pathway [169]. Additionally, a nanoformulation of this medication plus levodopa was recently suggested for the treatment of PD [170]. In a PD model, curcumin also offers protective effects on the cerebellum [171].…”
Section: Curcuminmentioning
confidence: 99%
“…In addition to the therapeutic application of Cur nanoformulations in AD, the existing literature supports Cur as a small molecular drug that reduces α-synuclein (α-syn) aggregates in the treatment of PD [ 103 , 104 ]. However, its low bioavailability and difficulty in crossing the BBB to accumulate at neuronal sites are the primary issues to be addressed in the development of Cur therapeutic strategies for PD.…”
Section: Cur Nanoformulations For Inflammatory Diseasesmentioning
confidence: 99%